2011
DOI: 10.1111/j.1365-2966.2011.18288.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical intraday variability studies of 10 low energy peaked blazars

Abstract: We have carried out optical (R band) intraday variability (IDV) monitoring of a sample of 10 bright low energy peaked blazars (LBLs). 40 photometric observations, of an average of ∼4 h each, were made between 2008 September and 2009 June using two telescopes in India. Measurements with good signal‐to‐noise ratios were typically obtained within 1–3 min, allowing the detection of weak, fast variations using N‐star differential photometry. We employed both structure function and discrete correlation function anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 114 publications
(141 reference statements)
3
40
0
Order By: Relevance
“…Small amplitude changes over a short time were reported (e.g. Moles et al 1986;Rani et al 2011). However, for the quasar, Fan et al (2009) also presented intra-day variations of 0.55 mag in 13 minutes and 0.81 mag in 116 minutes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small amplitude changes over a short time were reported (e.g. Moles et al 1986;Rani et al 2011). However, for the quasar, Fan et al (2009) also presented intra-day variations of 0.55 mag in 13 minutes and 0.81 mag in 116 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…The observed radiation is predominantly non-thermal Doppler boosted jet emission enhanced by that arising from shocks in the flows (Marscher & Gear 1985). Models based on the instabilities on the accretion disk could yield IDV when the blazar is in the low state, because in the low state, any contribution from the jets is weak (Rani et al 2011). For the quasar, the instabilities on the accretion disk could yield IDV in the modest state because it has obvious blue-bump emission.…”
Section: Presented Two Possible Variable Components (B and R)mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, microvariability is correlated with the flux gradients rather than specific flux states. Rani et al [14] reported the detection of microvariability with large DC in a sample of bright low-energy-peaked BL Lac sources (LBLs). Similarly, during their study of multiband optical flux and color variations of blazars on intraday and short term timescales of a few months, Gaur et al [15] found that the spectra of BL Lac sources often showed bluer-when-brighter trend whereas in flat spectrum radio quasars (FSRQ) the redder-when-brighter trend appears more frequent.…”
Section: Introductionmentioning
confidence: 99%
“…The source is categorized as a low synchrotron peaked blazar (LSP) by Abdo et al (2010a). The broadband spectrum, the correlation among multi-frequency flares, and the VLBI jet kinematics of the source were extensively studied in the past (e.g., Krichbaum et al 2001;Rani et al 2010Rani et al , 2011Soldi et al 2008;Savolainen et al 2010;Abdo et al 2010e, and references therein).…”
Section: Introductionmentioning
confidence: 99%